The Continuity of Errors and the Variability of Fate. Are we Learning about the Mistakes? - Sztobryn, Slawomir (Filosofiya osvity. Philosophy of Education, 2017)
The article analyzes the factors that have a significant influence on the truth (in the Aristotelian sense) of a biographical and autobiographical narrative. Restrictions emerging from the possibility of correct “reading” of the phenomena of our inner life and limitations associated with the so-called Experienced judgments are demonstrated. Biography could not avoid bio-socio-cultural conditions, as well as sphere of emotions, whose attributes can largely falsify reality, as well as its interpretation.